Analisis Motivasi Belajar Siswa Mata Pelajaran PJOK Ditinjau dari Gender, Aktivitas Fisik, dan Status Gizi - Permatasari, Putri Septiana Dwy Ayu; Wibowo, Sapto (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
The research aims to analyze the learning motivation of class VII students in the PJOK subject in lesson hours 7-9, which is influenced by gender factors, physical activity, and nutritional status. Research using the cross-sectional study method found that students' overall learning motivation was relatively low. The learning motivation of male students is higher (96) than female students (92). Students' physical activity is generally low (52%), with significant differences in learning motivation between physical activity categories. Most students' nutritional status is good (55%), with significant differences in learning motivation between nutritional status categories. Specifically, very low, moderate, and very low and high physical activity showed significant differences in learning motivation. Likewise, there is a comparison between poor and good nutritional status, less and more, and good and obesity. In conclusion, there are differences in student learning motivation between gender, physical activity and nutritional status. Male students' motivation tends to be higher, higher physical activity can increase learning motivation, and good dietary status supports learning motivation. Keywords: Nutritional Status, Physical Activity, Gender, Student Learning Motivation